Social Isolation Modulates CLOCK Protein and Beta-Catenin Expression Pattern in Gonadotropin-Inhibitory Hormone Neurons in Male Rats - Teo, Chuin Hau; Soga, Tomoko; Parhar, Ishwar S. (Frontiers in Endocrinology, 2017)
Post-weaning social isolation reduces the amplitude of the daily variation of CLOCK protein in the brain and induces lower reproductive activity. Gonadotropin-inhibitory hormone (GnIH) acts as an inhibitor in the reproductive system and has been linked to stress. Social isolation has been shown to lower neuronal activity of GnIH-expressing neurons in the dorsomedial hypothalamus (DMH). The exact mechanism by which social isolation may affect GnIH is still unclear. We investigated the impact of social isolation on regulatory cellular mechanisms in GnIH neurons. We examined via immunohistochemistry the expression of CLOCK protein at four different times throughout the day in GnIH cells tagged with Enhanced Fluorescent Green Protein (EGFP-GnIH) in 9-week old adult male rats that have been raised for 6 weeks under post-weaning social isolation and compared them with group-raised control rats of the same age. We also studied the expression of β-catenin – which has been shown to be affected by circadian proteins such as Bmal1 – in EGFP-GnIH neurons to determine if it could play a role in linking CLOCK in GnIH neurons. We found that social isolation modifies the pattern of CLOCK expression in GnIH neurons in the DMH. Socially isolated rats displayed greater CLOCK expression in the dark phase while control rats displayed increased CLOCK expression in the light phase. Furthermore, β-catenin expression pattern in GnIH cells was disrupted by social isolation. This suggests that social isolation triggers changes in CLOCK and GnIH expression, which may be associated with a rise in nuclear β-catenin during the dark phase.